Protocol for preparing and using a task to study “delayed safety-seeking behavior” in rats - Junghwa Lee; Sukwoo Choi (STAR Protocols)
Summary: The study of defensive behaviors in predicting action outcomes in novel situations without trial and error is limited by the lack of appropriate animal models. Here, we present a protocol for preparing and using a delayed safety-seeking task where rats temporarily hold information for future safety seeking. We describe steps for constructing a two-compartment chamber and provide testing procedures during which either in vivo recordings or optogenetics can be performed. This protocol is applicable for further research on defensive behavior.For complete details on the use and execution of this protocol, please refer to Han et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.